Legalizing prostitution: from illicit vice to lawful business - Weitzer, Ronald (New York University Press, 2013)
Some towns in Nevada have legal brothels where sex can be bought lawfully, yet in Las Vegas, prostitutes and their patrons are regularly prosecuted for exchanging sex for money, just as they are elsewhere in the United States. While sex work has long been controversial, it has become even more contested over the past decade as laws, policies, and enforcement practices have become more repressive in many nations, partly as a result of the ascendancy of interest groups committed to the total abolition of the sex industry. Legalizing Prostitution maps out the current terrain. Using America as a backdrop, Weitzer draws on extensive field research in the Netherlands, Belgium, and Germany to illustrate alternatives to American-style criminalization and marginalization of sex workers. These cases are then used to develop a roster of "best practices" that can serve as a model for other nations considering legalization. Legalizing Prostitution provides a theoretically grounded comparative analysis of political dynamics, policy outcomes, and red-light landscapes in nations where prostitution has been legalized and regulated by the government, presenting a rich and novel portrait of the multifaceted world of legal sex for sale.